Decreased Vacuolar Ca2+ Storage and Disrupted Vesicle Trafficking Underlie Alpha-Synuclein-Induced Ca2+ Dysregulation in S. cerevisiae - Callewaert, Geert; D’hooge, Petra; Ma, Tien-Yang; Del Vecchio, Mara; Van Eyck, Vincent; Franssens, Vanessa; Winderickx, Joris (Frontiers in Genetics, 2020)
The yeast Saccharomyces cerevisiae is a powerful model to study the molecular mechanisms underlying α-synuclein (α-syn) cytotoxicity. This is due to the high degree of conservation of cellular processes with higher eukaryotes and the fact that yeast does not endogenously express α-synuclein. In this work, we focused specifically on the interplay between α-syn and intracellular Ca2+ homeostasis. Using temperature-sensitive SEC4 mutants and deletion strains for the vacuolar Ca2+ transporters Pmc1 and Vcx1, together with aequorin-based Ca2+ recordings, we show that overexpression of α-syn shifts the predominant temporal pattern of organellar Ca2+ release from a biphasic to a quasi-monophasic response. Fragmentation and vesiculation of vacuolar membranes in α-syn expressing cells can account for the faster release of vacuolar Ca2+. α-Syn further significantly reduced Ca2+ storage resulting in increased resting cytosolic Ca2+ levels. Overexpression of the vacuolar Ca2+ ATPase Pmc1 in wild-type cells prevented the α-syn-induced increase in resting Ca2+ and was able to restore growth. We propose that α-syn-induced disruptions in Ca2+ signaling might be an important step in initiating cell death.